2012
DOI: 10.5116/ijme.50c3.2f27
|View full text |Cite
|
Sign up to set email alerts
|

Sources of variability in medical student evaluations on the internal medicine clinical rotation

Abstract: Objectives: To explore the sources of variability in evaluator ratings among third year medical students in the Internal Medicine clinical rotation. Also, to examine systematic effects and variability introduced by differences in the various student, evaluator, and evaluation settings. Methods: A multilevel model was used to estimate the amount of between-student, between-rater and raterstudent interaction variability present in the students' clinical evaluations in a third year internal medicine clinical rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…24 No gender difference was found in achievements in all parts of the final year examination in Kerbala Medical College and this was similar to the findings in many studies in other countries. [25][26][27] However, female students were consistently found in the literature to perform better than males in their medical training which might be related to higher motivation. A systematic review by Ferguson and his colleagues reported that a growing body of research explores whether different motivational, academic, and demographic factors influence the performance of male and female women where motivation seems to be important.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…24 No gender difference was found in achievements in all parts of the final year examination in Kerbala Medical College and this was similar to the findings in many studies in other countries. [25][26][27] However, female students were consistently found in the literature to perform better than males in their medical training which might be related to higher motivation. A systematic review by Ferguson and his colleagues reported that a growing body of research explores whether different motivational, academic, and demographic factors influence the performance of male and female women where motivation seems to be important.…”
Section: Discussionmentioning
confidence: 92%
“…25 Multivariate regression analysis approach to studying predictors of success in medical training was suggested in a systematic review of about twenty two thousands medical students (21) . Predictors are likely to be inter-correlated, as are outcome measures.…”
Section: Researchmentioning
confidence: 99%
“…In a study of internal medicine clerkship evaluations, there was greater variance in the scoring between evaluators than in scores between students. 4 This implies that variance in clinical performance scores depends more heavily on the evaluator than truly on student performance.…”
Section: Introductionmentioning
confidence: 99%